Estudo da população com Transtorno do Espectro Autista atendida em clínica suplementar de Belo Horizonte no ano de 2023 - Susana Satuf Rezende Lelis (2024)
The current diagnostic criteria of Autism Spectrum Disorder (ASD) is based on the Diagnostic and Statistical Manual of Mental Disorders (DSM 5). Being a global disorder of neurodevelopment, social reciprocity and communication, with repetitive behaviors, restricted interests and behavioral inflexibility. The diagnosis of ASD has been increasing throughout the world, bringing a new reality to families, changing their emotional, social and financial dynamics. This study aimed to outline a profile and demonstrate the main difficulties and repercussions of caring for people diagnosed with Autism Spectrum Disorder (ASD) and their families. This was a study carried out through data collection in the months of September and October 2023 in four multidisciplinary ASD treatment clinics in supplementary health. Quantitative and qualitative data were collected from 208 families, with the quantitative data presented in percentages in tables containing: current age of the patient, age at the beginning of therapies and age of caregivers; race of patients, sex of patient and caregivers, age of parents at conception, education of caregivers, type of birth, family income, educational background of the caregiver, presence or absence of declared faith and marital status of the caregiver (the last two considered as family resilience factors). The qualitative data were worked through Bardin's content analysis, illustrating and helping to better understand family demands and their dynamics. The results found agree, in part, with the profile of the ASD population reported in the literature, but with particularities such as, for example, in reference to the age of the parents at the conception of the ASD child and the number of diagnoses in females. It was also possible to identify factors of family resilience, such as the structure of family dynamics and the presence of a religion/faith. Based on the hypothesis that the presence of a member with ASD has an impact on the entire family, the author hopes to contribute to the construction of public policies and institutions to support ASD, guiding more assertive behaviors in meeting the needs of this population; minimizing the impacts of violence suffered through exclusion, economic and social difficulties.